2022
DOI: 10.3390/antiox11030467
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Phenolic Compounds from Lingonberry (Vaccinium vitis-idaea L.): Extraction, Chemical Characterization, Fractionation and Cellular Antioxidant Activity

Abstract: Lingonberries contain high contents of bioactive compounds such as chlorogenic acids and anthocyanins. In addition to radical scavenging and antioxidant activities, these compounds can protect cells from DNA damage. For this reason, lingonberries might be well suited for nutraceuticals or natural biomedicines. To assess these applications, the present study characterized and identified the most effective extract, only consisting of anthocyanins, copigments or a mixture of both, obtained from a lingonberry juic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…nidin-3-glucoside (Peak 2) and cyanidin-3-arabinoside (Peak 3) (Figure 1). This finding is in agreement with the results obtained by other researchers [12][13][14].…”
Section: Effect Of Sweeteners On the Stability Of Anthocyanins From L...supporting
confidence: 94%
“…nidin-3-glucoside (Peak 2) and cyanidin-3-arabinoside (Peak 3) (Figure 1). This finding is in agreement with the results obtained by other researchers [12][13][14].…”
Section: Effect Of Sweeteners On the Stability Of Anthocyanins From L...supporting
confidence: 94%
“…Cranberry ( Vaccinium macrocarpon ) and blueberry ( Vaccinium myrtillus ) showed high radical-scavenging properties in a xanthine/xanthine oxidase system that generates superoxide radicals, achieving IC 50 values of 27 µg/mL for cranberry juice and 7 µg/mL for blueberry juice [ 37 ]. Assays on human hepatoma cells (HepG2) showed that acidified ethanol extracts from lingonberry ( Vaccinium vitis-idaea ) protected cells from oxidative damage caused by ROS generated by H 2 O 2 , confirming that the antioxidants present in berry-type fruits can protect cells from oxidative stress by acting synergistically [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparison and correlation studies revealed that the results acquired from CV technique were found to be most compatible with Ferric reducing antioxidant power (FRAP) assay among all other spectroscopic and chromatographic techniques. The literature survey further indicated that the peak current, the area under the current curve, and peak potential are the most important parameters for studying the AOC of the extract [ 76 , 77 ]. The peak potential of the acquired phytochemicals correlates with the type of the reducing agent utilized [ 78 ].…”
Section: Applications Of the Electrochemical Methods For The Aocmentioning
confidence: 99%